Sensitive mass spectrometric assay for determination of 15-deoxy-Δ12,14-prostaglandin J2 and its application in human plasma samples of patients with diabetes - Morgenstern, Jakob; Fleming, Thomas; Kadiyska, Ivelina; Brings, Sebastian; Gröner, Jan; Nawroth, Peter Paul; Hecker, Markus; Brune, Maik (Analytical and bioanalytical chemistry, 2018)
The determination of individual prostaglandins (PG) in humans is mainly performed in urine samples. The quantification of PGs in human plasma could improve the understanding of particular PG species under various physiological and pathological conditions. 15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) is a dehydrated downstream product of PGD2 and is of high interest due to its recently discovered anti-inflammatory effects. Increasing availability of highly sensitive mass spectrometry allows the quantification of low abundant biomarkers like 15d-PGJ2 in human plasma samples. Herein, a sensitive LC-MS/MS method for the determination of 15d-PGJ2 was established. The method was validated according to the guidance of the American Food and Drug Administration and tested in plasma samples from patients with poorly controlled diabetes, considered to be a pro-inflammatory condition. Extraction of 15d-PGJ2 was achieved with an easy-to-use liquid-liquid extraction by ethyl acetate following a methanol precipitation. The lower limit of quantification was 2.5 pg mL−1 and linearity (R 2 = 0.998) was guaranteed between 2.5 and 500 pg mL−1 for 15d-PGJ2. Selectivity was assured by the use of two individual mass transitions (qualifier and quantifier). Precision and accuracy were validated in an inter- and intraday assay with a coefficient of variation below 11.8% (intraday) and 14.7% (interday). In diabetic patients with an HbA1C > 9%, increased plasma concentrations of 15d-PGJ2 compared to control plasma were measured. 15d-PGJ2 correlated negatively with the inflammation marker C-reactive protein. The developed LC-MS/MS method represents a new possibility to quantify 15d-PGJ2 with high specificity in human plasma samples. This may contribute to a better understanding of the potential anti-inflammatory effects of 15d-PGJ2 in severe long-term pro-inflammatory disorders like diabetes, cancer, or cardiovascular disease.